I/O consolidation in the data center : a complete guide to data center Ethernet and Fibre Channel over Ethernet - Gai, Silvano (Cisco Press networking technology series., 2010)
Using Fibre Channel over Ethernet (FCoE) and related technologies, data centers can consolidate data traffic onto a single network switch, simplifying their environments, promoting virtualization, and substantially reducing power and cooling costs. This emerging technology is drawing immense excitement, but few enterprise IT decision-makers and implementers truly understand it. I/O Consolidation in the Data Center is the only complete, up-to-date guide to FCoE. FCoE innovators Silvano Gai and Claudio DeSanti (chair of the T11 FCoE standards working group) systematically explain the technology: its benefits, tradeoffs, and what it will take to implement it successfully in production environments. Unlike most other discussions of FCoE, this book fully reflects the final, recently-approved industry standard. The authors also present five detailed case studies illustrating typical FCoE adoption scenarios, as well as an extensive Q and A section addressing the issues enterprise IT professionals raise most often. This is a fully updated version of Silvano Gai's privately-published book on FCoE, written for leading FCoE pioneer Nuova Systems before the company was acquired by Cisco. Nearly 12,000 copies of that book have already been distributed, demonstrating the immense interest in FCoE technology, and the scarcity of reliable information that has existed about it.